![(x^{2}+2x)^{2}-2(x^{2}+2x)*3=0 \\(x^{2}+2x)^{2}-2(x^{2}+2x)=0 \\x^{4}+4x^{2}-2x^{2}-4x=0 \\x^{4}+2x^{2}-4=0 (x^{2}+2x)^{2}-2(x^{2}+2x)*3=0 \\(x^{2}+2x)^{2}-2(x^{2}+2x)=0 \\x^{4}+4x^{2}-2x^{2}-4x=0 \\x^{4}+2x^{2}-4=0](https://tex.z-dn.net/?f=%28x%5E%7B2%7D%2B2x%29%5E%7B2%7D-2%28x%5E%7B2%7D%2B2x%29%2A3%3D0+%5C%5C%28x%5E%7B2%7D%2B2x%29%5E%7B2%7D-2%28x%5E%7B2%7D%2B2x%29%3D0+%5C%5Cx%5E%7B4%7D%2B4x%5E%7B2%7D-2x%5E%7B2%7D-4x%3D0+%5C%5Cx%5E%7B4%7D%2B2x%5E%7B2%7D-4%3D0)
x
4
+
2
x
2
-
4
= 0
Сделаем замену
y
=
x
2, тогда биквадратное уравнение примет вид
y
2
+
2
y
-
4
= 0
Для решения этого квадратного уравнения найдем дискриминант:
D = 22 - 4·1·(-4) = 20
y
1 =
-2 - √
20
≈ -3.2361
2·1
y
2 =
-2 + √
20
≈ 1.2361
2·1
x
2 =
-2 - √
20
2
x
2 =
-2 + √
20
2
x
1 =
(
-2 + √
20
)1/2
≈ 1.1118
2
x
2 =
-(
-2 + √
20
)1/2
≈ -1.1118
2